Battling With Books: The Gamification of an EFL Extensive Reading Class. (February 2022) - Freiermuth, Mark R.; Ito, Michiyo
Background: Extensive reading (ER) classes have become a popular way to promote reading in EFL (English as a Foreign Language) classrooms because ER supports the idea of reading for pleasure. However, reading in the classroom can still become stale if students have little chance to reflect on what they have read or if they become burdened by the reading requirements. Aim: In an attempt to create a more energetic ER classroom, we converted the classroom into a game-based environment with the aim of promoting L2 reading enjoyment and motivating students to read in a more focused manner . Method: As for specifics, 55 female Japanese university students—divided into two groups based upon English proficiency—participated in a social book reading game called Bibliobattle whereby students discussed their favorite books in small groups. Three iterations of the game were incorporated into the ER classroom as a way to enliven reading activities. Results: The game proved largely successful. From the data obtained in the debriefing questionnaires, students mentioned that they were motivated by the activities through reflection on their book's content and through the sharing of specific details about what they had read with their peers. Although both groups of students indicated their motivation to play the game, this was especially true for the lower level readers—a group that had demonstrated more apathy towards ER in the past. Based upon our experiences while running the game, we recommend that Bibliobattles be implemented as specialized events in the ER classroom as a means to help stimulate a love for reading in a second language; however, it should also be noted that student preparation for such battles is time-consuming, so the number of battles per semester should be limited to a maximum of two per semester.